Improved all-polymer solar cell performance of n-type naphthalene diimide-bithiophene P(NDI2OD-T2) copolymer by incorporation of perylene diimide as coacceptor - Sharma, Sandeep; Kolhe, Nagesh B.; Gupta, Vinay; Bharti, Vishal; Sharma, Abhishek; Datt, Ram; Chand, Suresh; Asha, S. K. (Macromolecules, 2016)
Naphthalene diimide-bithiophene P(NDI2OD-T2) is a well-known donor-acceptor polymer, previously explored as n-type material in all-polymer solar cells (all-PSCs) and organic field effect transistor (OFETs) applications. The optical, bulk, electrochemical, and semiconducting properties of P(NDI2OD-T2) polymer were tuned via random incorporation of perylene diimide (PDI) as coacceptor with naphthalene diimide (NDI). Three random copolymers containing 2,2'-bithiophene as donor unit and varying compositions of naphthalene diimide (NDI) and perylene diimide (xPDI, x = 15, 30, and 50 mol % of PDI) as two mixed acceptors were synthesized by Stille coupling copolymerization. Proton NMR spectra recorded in CD Cl-3 showed that the pi-pi stacking induced aggregation among the naphthalene units could be successfully disrupted by the random incorporation of bulky PDI units. The newly synthesized random copolymers were investigated as electron acceptors in BHJ all-PSCs, and their performance was compared with P(NDI2OD-T2) as reference polymer. An enhanced PCE of 5.03% was observed for BHJ all-PSCs (all-polymer solar cells) fabricated using NDI-Th-PDI30 as acceptor and PTB7-Th as donor, while the reference polymer blend with the same donor polymer exhibited PCE of 2.97% efficiency under similar conditions. SCLC bulk carrier mobility measured for blend devices showed improved charge mobility compared to reference polymer, with PTB7-Th:NDI-Th-PDI30 blend device exhibiting the high hole and electron mobility of 4.2 x 10(-4) and 1.5 x 10(-4) cm(2)/(V s), respectively. This work demonstrates the importance of molecular design via random copolymer strategy to control the bulk crystallinity, compatibility, blend morphology, and solar cell performance of n-type copolymers.

Naphthalene diimide copolymers by direct arylation polycondensation as highly stable supercapacitor electrode materials - Sharma, Sandeep; Soni, Roby; Kurungot, Sreekumar; Asha, S. K. (Macromolecules, 2018)
Conjugated donor-acceptor copolymers based on naphthalene diimide (NDI) as acceptor and thiopheneterminated oligophenylenevinylene as donor moieties (P-1 and P-2, respectively) were synthesized using the direct (hetero) arylation (DHAP) polymerization route. Nitrile groups were introduced at the vinylene linkage in one copolymer (P-2) to fine-tune its electrochemical properties. Both polymers show) pi-pi* transition in the 300-480 nm region and intramolecular charge transfer (ICT) from thiophene to NDI in the 500-800 nm region in the absorption spectra. P-2 exhibits a blue-shifted intramolecular charge transfer (ICT) band in the absorption spectrum as well as a lower reduction potential in the cyclic voltammogram compared to the analogous polymer without the nitrile substitution (P-1). The two polymers were evaluated as type III supercapacitor materials by preparing composite electrodes with carbon nanotubes (CNTs) and employing 0.5 M H2SO4 as the electrolyte. Their performance was compared with that of P(NDI2OD-T2) as a reference polymer. The polymer P-2 based supercapacitor exhibits a specific capacitance of 124 F/g with excellent stability up to 5000 cycles with almost 100% retention of the initial capacitance in the potential window of -0.7 to 0.5 V. Compared to P-2, P-1 exhibits a specific capacitance of 84 F/g, while the corresponding value for the reference polymer P(NDI2OD-T2) is 61 F/g under identical conditions.

High-voltage non-aqueous hybrid supercapacitor based on the N2200 polymer supported over multiwalled carbon nanotubes - Wavhal, Bhaiyyasaheb Anurath; Ghosh, Meena; Sharma, Sandeep; Kurungot, Sreekumar; Asha, S. K. (Nanoscale, 2021)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, is a widely accepted non-fullerene acceptor polymer that is used prominently in the energy harvesting application due to its ease of synthesis, high electron mobility, and other desirable semiconducting properties. With its recent foray into energy storage applications, there is tremendous potential for developing composites of N2200 with carbon nanotubes (CNTs) to improve its electrical properties and extend its applicability. Here we report a facile synthesis of an N2200 composite with multiwalled carbon nanotubes (MWCNTs) following an in situ approach to include MWCNTs into the polymer matrix, improving its electrochemical performance in an organic electrolyte (1 M LiClO4/propylene carbonate). The composite material with an optimum MWCNT content exhibits prominent redox behavior delivering a specific capacity of 80 mA h g((polymer))(-1) in a standard three-electrode cell. Moreover, the N2200/MWCNT composite material showing a battery-type electrochemical signature could perform as an efficient negative electrode in a high-voltage (2.4 V) hybrid supercapacitor device comprising capacitive activated carbon as the positive electrode.